Determinants of Food Service Attributes at School Canteen towards Secondary School Students’ Satisfaction Level in Pontian, Johor. - Abd Ghani, Fatimah; Abdul Rahman, Nur Aina Najwa; Hairul Izuan, Umaira Nur Miza; Ramli, Noorazlin (Journal of Islamic, Social, Economics and Development, 2025)
School canteens are vital in supporting students’ well-being and academic performance in Malaysia. This study examines the determinants of food service attributes—food and beverages, service quality, and physical environment—on secondary school students’ satisfaction levels in rural Pontian, Johor. Using a quantitative approach, structured questionnaires collected data from 342 students across four secondary schools. Descriptive and correlation analyses revealed that service attributes (e.g., staff responsiveness, cleanliness, and friendliness) emerged as the most influential factor in student satisfaction, surpassing food quality and environmental comfort. These findings highlight the critical role of interpersonal service delivery in school canteens, even in resource-limited rural settings. The study provides actionable insights for canteen operators and school administrators to prioritize staff training, service efficiency, and menu improvements. This research contributes to broader efforts to enhance student well-being and engagement in Malaysian schools by aligning food service practices with student expectations.